Mekanisme Dampak Negatif Akrilamida Pada Pencemaran Lingkungan Dan Terjadinya Penyakit Kanker: Review - Ayub; Anna Heirina; Refa Riskiana (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
Acrylamide is a chemical that is formed naturally from heating starchy or carbohydrate foods at a temperature of 120 ºC. Some of the uses of acrylamide include water treatment, oil drilling, pulp and paper, mining, and others. Acrylamide pollution in the environment can be through surface water or groundwater, water channels that flow into wells, rivers, to the sea. Several studies have reported an increased risk of kidney disorders, endometrial cancer, and ovarian cancer as a result of exposure to acrylamide. The mechanism for the occurrence of cancer due to acrylamide is the occurrence of genesis mutations or glycidamide mutations, these mutations which cause cancer. Research shows that glycidamide mutations are found in one-third of the approximately 1,600 tumor genomes corresponding to 19 human tumor types from 14 organs. There is an unexpected extensive contribution of acrylamide-associated mutagenesis in human cancer.